2021
DOI: 10.1038/s41433-021-01688-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolving treatment paradigms for PCV

Abstract: Polypoidal choroidal vasculopathy (PCV) is a subtype of neovascular AMD (nAMD) that accounts for a significant proportion of nAMD cases worldwide, and particularly in Asia. Contemporary PCV treatment strategies have closely followed those used in typical nAMD, though there are significant gaps in knowledge on PCV management and it remains unclear if these strategies are appropriate. Current clinical trial data suggest intravitreal anti-vascular endothelial growth factor (VEGF) therapy alone or in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 100 publications
2
24
0
Order By: Relevance
“…Differently expressed mRNAs including ENSG00000249572, miRNA has-miR-20a-5p in peripheral blood mononuclear cells found were to be predictors for good and poor responders to anti-VEGF therapy in patients with nAMD ( 35 ). Furthermore, OCT and OCT angiography characteristics have been used as biomarkers for diagnosis and treatment on PCV and nAMD ( 36 ). The height of the pigment epithelium detachment (PED) and reflectivity of the content of the PED may predict polypoidal lesions closure ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differently expressed mRNAs including ENSG00000249572, miRNA has-miR-20a-5p in peripheral blood mononuclear cells found were to be predictors for good and poor responders to anti-VEGF therapy in patients with nAMD ( 35 ). Furthermore, OCT and OCT angiography characteristics have been used as biomarkers for diagnosis and treatment on PCV and nAMD ( 36 ). The height of the pigment epithelium detachment (PED) and reflectivity of the content of the PED may predict polypoidal lesions closure ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OCT and OCT angiography characteristics have been used as biomarkers for diagnosis and treatment on PCV and nAMD ( 36 ). The height of the pigment epithelium detachment (PED) and reflectivity of the content of the PED may predict polypoidal lesions closure ( 36 ). Re-examining the baseline scans for an inverted U-shaped elevation in anti-VEGF resistant cases was helpful for detecting polypoidal lesions closure ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polypoidal choroidal vasculopathy (PCV) is considered a variant of nAMD characterised by polypoidal dilation with a branching neovascular network usually located between Bruch’s membrane and RPE. 12 , 13 The presence of polypoidal lesions is best detected using indocyanine green angiography (ICGA). 14 Unlike typical AMD, drusen are absent in PCV and recurrent subretinal haemorrhages and serous retinal detachments are the most common clinical findings.…”
Section: Introduction To Degenerative Macular Disorders and Their Man...mentioning
confidence: 99%
“…Polypoidal choroidal vasculopathy (PCV) is now recognized as a subtype of neovascular age-related macular degeneration (nAMD) with specific and distinct characteristics on indocyanine angiography (ICGA) and optical coherence tomography (OCT). [ 1 2 3 ] Though treatment of PCV and nAMD involves the use of intravitreal anti-vascular growth factor (anti-VEGF) agents for disease control, it is still important to distinguish between these due to differences in response to anti-VEGF, with PCV eyes showing a suboptimal response[ 3 ] and higher risk of recurrence in the same and other eye in PCV as opposed to nAMD. [ 4 ] Additionally, the higher predilection of PCV to cause massive and blinding subretinal hemorrhages is another cause of concern.…”
mentioning
confidence: 99%
“…The management of PCV has evolved over the past decade with the availability of more potent anti-VEGF agents that have better penetration through the retinal pigment epithelium (RPE) and higher affinity to inhibit the action of VEGF. [ 1 2 ] After the recommendations of the PLANET clinical trial,[ 6 ] which showed excellent outcomes in PCV eyes receiving intravitreal aflibercept monotherapy, and with nonavailability of the Visudyne dye in many parts of the world, the trend in management is gravitating toward anti-VEGF monotherapy for PCV. However, the treatment burden remains significantly high, and until recently, aflibercept was considered to be the drug of choice for management of eyes with PCV in view of its higher efficacy in polyp regression compared to ranibizumab.…”
mentioning
confidence: 99%